Peranan Hardiness Terhadap Stress Akademik pada Siswa Kelas XI - Krisnova Nastasia; Ifani Candra; Annisa Kurnia Putri (Psyche 165 Journal, 2023)
In taking education there must be a lot of problems faced by students, especially when they are in the phase of adolescent development which is a transitional period. This study aims to determine how big the relationship between hardiness and academic stress in class XI students of SMA Negeri 4 in Padang. The independent variable in this study is hardiness and the dependent variable in this study is academic stress. The measuring tools used in this research are the hardiness scale and the academic stress scale which the researchers constructed themselves based on the theoretical concepts used where for the hardiness scale uses the theoretical concepts covering three aspects, namely commitment, control, and challenge. Academic stress uses the theoretical concept which includes four aspects, namely biological, cognitive, emotional and behavioral. The sample collection technique in this study used a simple random sampling technique. The sample in this study amounted to 153 students who were in SMA Negeri 4 Padang. The validity test in this study is to use content validity and construct validity. The validity coefficient results obtained on the hardiness scale moved from rxy = 0.352 to rxy = 0.830 with a reliability coefficient α = 0.917, while the validity coefficient on the academic stress scale moved from rxy = 0.348 to rxy = 0.822 with a reliability coefficient α = 0.941. Based on data analysis, a correlation value of r = -0.535 was obtained with a significance level of p = 0.000, meaning that the hypothesis was accepted. This shows that there is a moderate and very significant relationship between hardiness and academic stress in class XI students of SMA Negeri 4 Padang with a negative relationship. The effective contribution of hardiness to academic stress is 29% while 71% is influenced by other factors.